Hukum Waris Mazhab Negara: Sebuah Tinjauan Sisi Maslahah (Studi Analisis Pemikiran Hazairin dan KHI) - Defel Fakhyadi (JURNAL INDO-ISLAMIKA, 2014)
This article proves that the modernization of inheritance law is a form of reformation in Islamic law by taking into account the sociological condition of the society to achieve maslahah (maqasid al-shariah). Islamic inheritance law is influenced by the Arabic inheritance law in the pre-Islam era that followed patrilineal system, which influenced the mainstream thoughts of Islamic scholars in understanding inheritance law. This, in turn, resulted in patriarchal Islamic inheritance law. For that reason, it is necessary to re-interpret the law in order to construct a comprehensive fiqh (Islamic law). Hazairin’s thoughts are a revolutionary of inheritance law in Indonesia, such as bilateral inheritance, ahli waris pengganti and kala>lah. Some inheritance law reform contained in KHI are not addressed in conventional fiqh, because there are several aspects to be taken by Indonesian scholars whose ideas are not in conflict with the principles of Sharia (maslahah).